2020
DOI: 10.33448/rsd-v9i7.4242
|View full text |Cite
|
Sign up to set email alerts
|

Compostos bioativos presentes em couve-manteiga (Brassica oleracea L.) em três estádios de desenvolvimento e comparação das suas capacidades antioxidantes

Abstract: Young vegetables are gaining more and more popularity on a world scale, not only because they are highly nutritious foods, but because they constitute a new ingredient, being used to improve the visual aspect of salads and other garnishes and to embellish a wide variety of dishes. This study aimed to compare the content of bioactive compounds and the antioxidant capacity of kale (Brassica oleracea L.) in three growth stages: microgreen (15 days after sowing), baby leaf (40 days after sowing) and adult (60 days… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…We concluded that, in addition to the genetic variability existing among genotypes, the cultivation system also influences the concentration of bioactive compounds. Moreover, other factors such as part of the plant, phenological stage and crop management can also influence the concentration of these bioactive compounds (Rigueira et al, 2016;Batista et al, 2017;Nasser et al, 2020;Zanzini et al, 2020). The two first main components (PC1 and PC2) showed a total of 70.7 and 21.8% of total variation, respectively (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…We concluded that, in addition to the genetic variability existing among genotypes, the cultivation system also influences the concentration of bioactive compounds. Moreover, other factors such as part of the plant, phenological stage and crop management can also influence the concentration of these bioactive compounds (Rigueira et al, 2016;Batista et al, 2017;Nasser et al, 2020;Zanzini et al, 2020). The two first main components (PC1 and PC2) showed a total of 70.7 and 21.8% of total variation, respectively (Figure 2).…”
Section: Resultsmentioning
confidence: 98%
“…acephala) is one of Brazil's most cultivated and consumed plant. It contains a high concentration of nutrients, namely iron, vitamins, and vegetable fibers that contribute to better intestinal flow functioning, regulate blood sugar and help lower cholesterol [4][5][6].…”
Section: Introductionmentioning
confidence: 99%